Tinjauan Yuridis terhadap Penegakan Tindak Pidana Terorisme Ditinjau dari â€œAsas Presumtion of Innocenceâ€ dan â€œPresumtion of Guiltâ€ - I Made Yogi Astawa; I Made Minggu Widyantara; Ni Made Sukaryati Karma (Warmadewa Press, 2020)
Terrorism is an act that uses violence or threat of violence. Thus, law enforcement against criminal acts of terrorism is carried out with the Indonesian Criminal Justice System, with the operation of criminal justice systems ranging from the level of investigation, prosecution, justice to Prisoners in Penitentiary institutions into a single unit of the criminal justice system that enforces legal rules related to criminal acts of terrorism based on the principles of